Polymerization-induced self-assembly and disassembly during the synthesis of thermoresponsive ABC triblock copolymer nano-objects in aqueous solution. Issue 24 (8th June 2022) - Varlas, Spyridon; Neal, Thomas J.; Armes, Steven P.
Abstract : Chain extension of linear AB diblock copolymer vesicles by seeded RAFT aqueous dispersion polymerization using a hydrophilic monomer C leads to polymerization-induced disassembly to form lower-order thermoresponsive ABC triblock copolymer nano-objects. Abstract : Polymerization-induced self-assembly (PISA) has been widely utilized as a powerful methodology for the preparation of various self-assembled AB diblock copolymer nano-objects in aqueous media. Moreover, it is well-documented that chain extension of AB diblock copolymer vesicles using a range of hydrophobic monomers via seeded RAFT aqueous emulsion polymerization produces framboidal ABC triblock copolymer vesicles with adjustable surface roughness owing to microphase separation between the two enthalpically incompatible hydrophobic blocks located within their membranes. However, the utilization of hydrophilic monomers for the chain extension of linear diblock copolymer vesicles has yet to be thoroughly explored; this omission is addressed for aqueous PISA formulations in the present study. Herein poly(glycerol monomethacrylate)-poly(2-hydroxypropyl methacrylate) (G-H) vesicles were used as seeds for the RAFT aqueous dispersion polymerization of oligo(ethylene glycol) methyl ether methacrylate (OEGMA). Interestingly, this led to polymerization-induced disassembly (PIDA), with the initial precursor vesicles being converted into lower-order worms or spheres depending on the target mean degree of polymerization (DP) for the corona-forming POEGMA block. Moreover, construction of a pseudo-phase diagram revealed an unexpected copolymer concentration dependence for this PIDA formulation. Previously, we reported that PHPMA-based diblock copolymer nano-objects only exhibit thermoresponsive behavior over a relatively narrow range of compositions and DPs (see Warren et al., Macromolecules, 2018, 51, 8357–8371). However, introduction of the POEGMA coronal block produced thermoresponsive ABC triblock nano-objects even when the precursor G-H diblock copolymer vesicles proved to be thermally unresponsive. Thus, this new approach is expected to enable the rational design of new nano-objects with tunable composition, copolymer architectures and stimulus-responsive behavior.